Anthropometric Design of a Patient Transfer Aid for Wheelchair to Bed Transfer: Enhancing Safety and Reducing Musculoskeletal Risk - Ziandra Indar Pratama; Franka Sukma; Wakhit Ahmad Fahrudin; Riki Effendi; Ahmad Yunus Nasution (DINAMIS, 2026)
This study develops an anthropometric-based patient transfer aid for wheelchair-to-bed transfer aimed at reducing musculoskeletal disorder (MSD) risk among healthcare workers. The research was conducted at Pesanggrahan Community Health Center involving 100 respondents whose anthropometric data were used as the basis for ergonomic design development, including body weight, hip width, elbow-to-elbow breadth, forearm length, foot length, and popliteal height. The collected data were analyzed using validity, reliability, adequacy, uniformity, and percentile methods (5th, 50th, and 95th percentiles) to ensure statistical robustness and to derive ergonomic design dimensions. The results were translated into engineering specifications, including a lifting capacity of 100 kg, base width of 50 cm, handle spacing of 43.2 cm, seat width of 25 cm, and minimum clearance of 45 cm. The proposed design was developed using solid works software through parametric 3D modeling and assembly integration to ensure geometric accuracy, structural feasibility, and functional system configuration. The design enables seated-position transfer without requiring patients to stand, improving usability for individuals with limited mobility and reducing caregiver physical strain. From an ergonomic perspective, the system is expected to reduce MSD risk by minimizing manual lifting, trunk flexion, and asymmetric loading during transfer activities. However, the study is limited to CAD-based design and does not yet include prototype fabrication or biomechanical validation. The findings demonstrate that integrating anthropometric data with SolidWorks-based engineering design provides an effective and practical approach for developing ergonomic patient transfer aids in healthcare environments.